SOBRE LAS ALTERACIONES CEREBRALES EN LAS PSICOSIS ALCOHOLICAS - NIETO, DIONISIO (Instituto Politécnico Nacional, CD MEXICO, DF, MEX, 1942)
The oxygen content of arterial and venous blood of the cerebral circulation was detd in dogs before and after exptl production of a lesion of the 4th ventricle to produce cerebral tumefaction In 3 of 8 expts the difference between the O2 content of ar
BOL INST ESTUD MED BIOL
Keywords: ALTERACIONES, CEREBRALES, PSICOSIS, ALCOHOLICAS; CIENCIAS MEDICAS; PSICOFARMACOLOGIA; ALCOHOLISMO